Supercritical fluid extraction of α - mangostin from mangosteen fruit rind (garcinia mangostana linn.) - Phung, Le Thi Kim.; Nam, Hoang Minh.; Tuyet, Nguyen Thi Ngoc.
The extraction of α-mangostin from mangosteen fruit rind Garcinia mangostana Linn cultivated in Vietnam using supercritical carbon dioxide with ethanol as a modifier was studied in this work. Experimental design was used to investigate the effect of operating pressure (20-30MPa), temperature (313-333 K), and solvent flow rate (10-20g/min) on the recovery and the selectivity of α-mangostin. Statistical analysis of experiments indicated that pressure and flow rate of solvent affected on the recovery of α-mangostin; with the selectivity of α-mangostin, pressure, solvent flow rate, temperature and interaction between these factors significantly affected. The central composite design showed that the polynomial regression models were in good agreement with the experimental results with the coefficients of determination from 0.9037 to 0.9666. Based on the proposed model, the optimal condition for extraction that was within the experimental range was found to be at lowest temperature 313 K, highest pressure 30 MPa and the nearly lowest flow rate of solvent 12.71 g/min. It was proved that the model equation developed can be used for predicting the extraction of α-mangostin from Garcinia mangostana Linn. The maximum recovery and selectivity of α-mangostin achieved at the optimal conditions was 22.83 mg/g material and 32.77%.
Keywords: Supercritical fluid extraction; SFE(Chemical extraction); Alpha mangostin; Garcinia mangostana linn; Mangosteen fruit rind